Improvement in the Performance of Direct Torque Control Induction Motor Drives - Mukherjee, Subhasish (My University, 2014)
In this work, we have studied different control strategies of induction motor drives and with the technological advancement, various command approaches have been developed by the scientific community to master in real time, the flux and the torque of the electrical machines, the direct torque control (DTC) scheme being one of the most proven steps in this direction. In principle, the motor terminal voltages and currents are sampled and used to estimate the motor flux and torque. Based on estimates of the flux position and the instantaneous errors in torque and stator flux magnitude, a voltage vector is selected to restrict the torque and the flux errors within their respective torque and flux hysteresis bands. In the conventional DTC, the selected voltage vector is applied for the whole switching period regardless of the magnitude of the torque error. This results in high torque ripple. A better drive performance can be achieved by varying the sector angle in modified DTC. The space vector modulation technique (SVPWM) is applied to 2 level inverter with 12 sectors angular control in the DTC drive system to reduce the torque ripple. The results are simulated and compared using the MATLAB/ Simulink.
M.E.(Power Systems & Drives
Keywords: Induction Motor; Direct Torque Control; Field Oriented Control; Voltage Source Inverter; SVPWM